Interart Poetics : Essays on the Interrelations of the Arts and Media - Hedling, Erik,; Lagerroth, Ulla-Britta,; Lund, Hans, (Faux Titre ;, 1997)
In this anthology are gathered 28 essays, devoted to the interrelations of the arts and media. They present together the current state of the emerging field of Interart Studies. The contributors - Stephen Greenblatt, Claus Clüver, Erika Fischer-Lichte, John Neubauer, Steven Paul Scher, Walter Bernhart, Ulrich Weisstein, Eric T. Haskell, Eric Vos, Thomas Elsaesser, among others - are leading international scholars in the fields of Art History, Literary Criticism, Musicology, Film, Theatre and Media Studies. In challenging ways they promote interdisciplinary strategies in the study of the traditional arts: dance, literature, music, painting, sculpture, theatre etc, as well as of the modern media: film, TV, video, computer-generated arts, etc. The essays collected engage in a broad perspective of topics, approached from varying theoretical, methodological or ideological viewpoints. No single thread runs through the diversely conceived essays, yet it is evident that what all contributors appear to envision is the importance today of investigations into the problems of what might be called the interart - or intermedia - discourse. Aimed at university teachers, scholars, students and even artists, this book will meet the demands from those interested in modern modes of interart and intermedia analysis.